REPORT OF THE ANNUAL CONVENTION. - Cox, Carson (The Accounting Review, 1959)
Abstract This article presents report of the 1958 annual convention of the American Accounting Association which offered an ideal opportunity to combine a first-class vacation trip with the meeting of friends and members of the Association. Special activities of the ladies' program included tours of the Onondaga Pottery Co., the Television Receiver Division of General Electric Company, the campus of Syracuse University, and the Oneida Community Silver plant, with luncheons and entertainment at the Sims Dining Hall and Drumlins Country Club. At the luncheon and business meeting on Wednesday, with President C.R. Niswonger presiding, brief reports were given by the Editor regarding "The Accounting Review," by the Secretary-Treasurer regarding finances and membership statistics, and by the Director of Research concerning the Association's activity in this area. A motion was made from the floor and carried accepting the report of the Committee on Nominations and instructing the Secretary-Treasurer to cast a unanimous ballot for election of the above-named persons.